(untitled) (Società e diritti, 2022)
The University of Milan is traditionally engaged in the activities of teacher training and, as regards initial training, has participated with punctual dedication to the activities required by the various governments that have occurred over time. And not only that. The Committee for Teacher Training, active for some time in the Lombardy University, has contributed proactively to the definition of training models and has participated in the debates that have developed both within the Italian Academy and in the ministerial, school and trade union environments. All this happened for one main reason: the possibility of exploiting real positive network economies connected with the size and, therefore, the heterogeneity of a large university. In this work, in particular, will be presented the experience of the University of Studies in relation to obtaining the certification provided for by Legislative Decree n.59 of 2017: through the data collected through this last experience, In fact, it will be possible to propose a series of considerations about the most diverse profiles of teaching candidates in the coming years in order to come up with a proposal for an efficient, effective and sustainable initial teacher education model. Keywords: Teacher education, Initial teacher training, University